The empowerment of intensive intermediate English II teachers’ development of listening activities using cognitive, metacognitive, and social affective strategies at the Western Multidisciplinary Campus of the University of El Salvador, semester I, 2016. - Acosta Moza, Rodrigo Antonio; Ruano Morán, Celia María; Vicente Ramírez, Carlos Adolfo (2024)
The researchers conducted the research project “The Empowerment of Intensive Intermediate English II Teachers’ Development of Listening Activities using Cognitive, Metacognitive, and Social Affective Strategies at the Western Multidisciplinary Campus of the University of El Salvador, Semester I, 2016.” Through this research work, the researchers intended to empower Intensive Intermediate English II teachers‟ listening strategies by making them aware of the usefulness cognitive, metacognitive, and social affective strategies have for students‟ listening improvement. That is why, the researchers developed a workshop in which Intensive Intermediate English II teachers were instructed on and provided with a series of cognitive, metacognitive, and social affective strategies for them to apply those strategies when working with listening tasks.